Interaction of rocuronium with human liver cytochromes P450 - Eva Anzenbacherova; Alena Spicakova; Lenka Jourova; Jitka Ulrichova; Milan Adamus; Petr Bachleda; Pavel Anzenbacher (Elsevier, 2015)
Rocuronium is a neuromuscular blocking agent acting as a competitive antagonist of acetylcholine. Results of an inhibition of eight individual liver microsomal cytochromes P450 (CYP) are presented. As the patients are routinely premedicated with diazepam, possible interaction of diazepam with rocuronium has been also studied. Results indicated that rocuronium interacts with human liver microsomal CYPs by binding to the substrate site. Next, concentration dependent inhibition of liver microsomal CYP3A4 down to 42% (at rocuronium concentration 189 μM) was found. This effect has been confirmed with two CYP3A4 substrates, testosterone (formation of 6β-hydroxytestosterone) and diazepam (temazepam formation). CYP2C9 and CYP2C19 activities were inhibited down to 75-80% (at the same rocuronium concentration). Activities of other microsomal CYPs have not been inhibited by rocuronium. To prove the possibility of rocuronium interaction with other drugs (diazepam), the effect of rocuronium on formation of main diazepam metabolites, temazepam (by CYP3A4) and desmethyldiazepam, (also known as nordiazepam; formed by CYP2C19) in primary culture of human hepatocytes has been examined. Rocuronium has caused inhibition of both reactions by 20 and 15%, respectively. The results open a possibility that interactions of rocuronium with drugs metabolized by CYP3A4 (and possibly also CYP2C19) may be observed.